FILSAFAT IBN THUFAYL DAN NOVEL HAYY BIN YAQDHAN - Muh. Syamsuddin (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2019)
Hayy bin Yaqdhan is a treatise aimed at providing a scientific explanation of the beginnings of human life on earth. This treatise is Ibn Thufayl’s presentation of knowledge, which seeks to harmonize Aristotle with Neo-Platonists on the one hand, and Al-Ghazali with Ibn Bajjah on the other. Ibn Thufayl followed the middle way, bridging the gap between the two parties.Hayy bin Yaqdhan is a thought experiment. It was built on Ibn Sina’s thought experiment about “Flying Man” which calls for a living human mind, driven by the Active Intellect, the principle by which God communicates His truth to the human mind and establishes order and intelligence to nature.The findings of Ibn Thufayl’s thought experiment with his fiction is that language, culture, religion, and tradition are not essential for the development of a perfect mind even, perhaps, blocking its progress. This result shows a hard slap for social structures that exist in general and specifically Institutional Islam. Social criticism, which complements Ibn Thufayl’s critical message, is not left implicit. The criticism was explained in the meeting between Hayy bin Yaqdhan and members of a society governed by the religion of prophetic revelation. Ibn Thufayl has expressed Neo-Platonism postulates about religious harmony and philosophy.